Real time noise suppression in social settings comprising a mixture of non-stationary and transient noise - Yong, Pei Chee; Nordholm, Sven (2017)
© 2016 IEEE. Hearable is a recently emerging term that describes a wireless earpiece that enhances the user's listening experience in various acoustic environment. Another important feature of hearable devices is their capability to improve speech communication in difficult social settings, which usually consist of a mixture of different non-stationary noise. In this paper, we present techniques to suppress a combination of non-stationary noise and transient noise. This is achieved by employing a combined noise suppression filter based on prediction and masking to achieve impulsive noise suppression. Experimental results highlight the robustness of the proposed algorithm in suppressing the transient noise while maintaining the speech components, without requiring any prior information of the noise.